Assessment of three GPM IMERG products for GIS-based tropical flood hazard mapping using analytical hierarchy process - Syakira, Nurul; Tan, Mou Leong; Zulkafli, Zed; Zhang, Fei; Tangang, Fredolin; Chang, Chun Kiat; Wan Ibrahim, Wan Mohd Muhiyuddin; P. Ramli, Mohd Hilmi (Multidisciplinary Digital Publishing Institute, 2023)
The use of satellite precipitation products can overcome the limitations of rain gauges in flood hazard mapping for mitigation purposes. Hence, this study aims to evaluate the capabilities of three global precipitation measurement (GPM) integrated multisatellite retrievals for GPM (IMERG) products in tropical flood hazard mapping in the Kelantan River Basin (KRB), Malaysia, using the GIS-based analytic hierarchy process (AHP) method. In addition to the precipitation factor, another eleven factors that contribute to flooding in the KRB were included in the AHP method. The findings demonstrated that the spatial pattern and percentage area affected by floods simulated under the IMERG-Early (IMERG-E), IMERG-Late (IMERG-L), and IMERG-Final (IMERG-F) products did not differ significantly. The receiver operating characteristics curve analysis showed that all three IMERG products performed well in generating flood hazard maps, with area under the curve values greater than 0.8. Almost all the recorded historical floods were placed in the moderate-to-very-high flood hazard areas, with only 1“2 found in the low flood hazard areas. The middle and lower parts of the KRB were identified as regions of very high" and "high" hazard levels that require particular attention from local stakeholders.